Managing problematic visual media in natural hazard emergencies. (1st June 2021) - Dootson, Paula; Thomson, T.J.; Angus, Daniel; Miller, Sophie; Hurcombe, Edward; Smith, Adam
Abstract: In natural hazard emergencies, visual media (images, videos) document and convey the possible risk, impact, and severity of the hazard. Issues arise when the visuals being circulated, at scale and speed, are manipulated, fake, or are from an unrelated event or location. These problematic visuals can impact how communities interpret the risk of an emergency. Further, when visual media present information (i.e. a cue) in conflict with what an emergency services agency is instructing the public to do, it can lead to uncertainty and confusion in the community on how to act. This research identifies four specific types of problematic visual media that are common to natural hazard emergencies in Australia. We propose a combination of reactive and proactive strategies that can be employed by emergency services agencies to manage the extent and impact of these problematic visuals.